2017
DOI: 10.11138/orl/2017.10.3.276
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Management of Patients With Oro-Maxillo-Facial Defects: A Long-Term Follow-Up Retrospective Study

Abstract: SUMMARYIntroduction. The aim of this study is to determine the outcome of maxillofacial prosthetic rehabilitation after oncological resections, including both intra-and extra-oral prosthetic devices. Methods. In this study were included 72 patients, who have undergone an intra or extra-oral maxillofacial prosthetic rehabilitation after an oncologic resection. Tumors on the head and neck were analyzed and the defects of these resections have been divided in two different groups: intra and extra-oral defects. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
0
17
0
5
Order By: Relevance
“…Currently, the literature of oral rehabilitation in HNC patients is mainly concerning the impact and side effects from radiation therapy and the usefulness of different rehabilitation methods, especially implants . Investigations in the field have shown that maxillofacial and oral rehabilitation are important ways to improve oral aesthetics, oral function and QoL after HNC treatment . However, data seem to be poor and conflicting in the field of oral rehabilitation of HNC patients, and especially knowledge of the difference in OHRQoL, aesthetics and functional outcome between HNC patients and non‐HNC patients is scarce, and more investigation is needed to make stronger conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the literature of oral rehabilitation in HNC patients is mainly concerning the impact and side effects from radiation therapy and the usefulness of different rehabilitation methods, especially implants . Investigations in the field have shown that maxillofacial and oral rehabilitation are important ways to improve oral aesthetics, oral function and QoL after HNC treatment . However, data seem to be poor and conflicting in the field of oral rehabilitation of HNC patients, and especially knowledge of the difference in OHRQoL, aesthetics and functional outcome between HNC patients and non‐HNC patients is scarce, and more investigation is needed to make stronger conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is a multidisciplinary branch which focuses on improving quality of life by preserving residual structures, restoring oral functions, and improving esthetic appearances [38]. The need for maxillofacial prostheses is increasing in recent years with the 6% increased prevalence of oral cancer, with the incidence being more in males in the ratio of 2:1 [39]. Maxillofacial defects can be classified as either intraoral or extraoral.…”
Section: Maxillofacial Prosthesesmentioning
confidence: 99%
“…Extraoral defects include any other part of the head and neck. This defect inclines more towards trauma and tumor resurrection [39]. The obturators are prosthesis used to close palatal defects after maxillectomy, to restore masticatory function and to improve speech.…”
Section: Maxillofacial Prosthesesmentioning
confidence: 99%
“…A reparação da perda facial, além de restaurar a aparência, protege os tecidos expostos, e tem a finalidade de promover a reintegração ao convívio social do individuo, reduzindo o sentimento de ansiedade possibilitando o surgimento moral do paciente. O tratamento reabilitador estende-se tanto às perdas intraorais, das fendas labiopalatais quanto às perdas extraorais (4). Todas as etapas e dimensões da reconstrução maxilofacial exigem uma elevada precisão e habilidade do profissional para alcançar um excelente resultado na reprodução anatômica e funcional da área afetada dos pacientes.…”
Section: Introductionunclassified